Case Report: BRCA1 and BRCA2 loss in a young man with primary cutaneous extraskeletal osteosarcoma - Luo, Wen-Feng; Hou, Yu-Hang; Huang, Yu-Teng; Lai, Jun-Dong; Jiang, Hui-Shan; Wang, Wei-Liang (Frontiers in Oncology, 2025)
BackgroundExtraskeletal osteosarcoma is an uncommon and high-grade soft tissue malignancy. The incidence is even lower when the skin is the primary site. To the best of our knowledge, the primary cutaneous osteosarcoma has fewer than 30 reported cases worldwide, which with decreased copy number ofBRCA1 and BRCA2 has never been reported before.Case presentationA 28-year-old man was hospitalized for a skin mass on the left shoulder. The histological examination showed a large number of tumor giant cells and fibroblasts, and nuclear division was easy to see. Immunohistochemistry showed positive for CK, EMA, S100, CD34, CK7, Bcl-2, ACTin, and NSE, and negative for Vim, SATB2, CD99, SMA (focal), and Ki67 was about 40%. Shoulder joint CT and PET-CT showed that no metastasis presented. Germline testing showed decreased copy number ofBRCA1 and BRCA2. The diagnosis was cutaneous extraskeletal osteosarcomas of the left shoulder. The patient underwent an enlarged resection, followed by local radiotherapy four cycles. No recurrence or metastasis occurred on a 1-year of follow-up.ConclusionsPrimary cutaneous extraskeletal osteosarcoma (PC-EOS) is rare, and preoperative differential diagnosis is difficult. This is the first report of PC-EOS with decreased copy number of BRCA1 and BRCA2. The presented case highlights the importance of accurate histopathological examination and comprehensive analysis. We considered that BRCA1 and BRCA2 genes may are associated with a worse outcome and local recurrence in PC-EOS. But, it may not have been fully recognized.